Gray matter alterations in first-admission adolescents with schizophrenia - Henze, Romy; Brunner, Romuald; Thiemann, Ulf; Parzer, Peter; Richterich, Andreas; Essig, Marco; Resch, Franz; Stieltjes, Bram (Journal of neuroimaging, 2011)
BACKGROUND AND PURPOSE Imaging studies of patients with schizophrenia have described a variety of cerebral alterations. However, long-term medication and the chronicity of the disorder may have contributed substantially to these alterations. Studies examining patients in the early stages of the disorder reduce the possibility of such confounding factors but are rare. In light of this, the aim of the present study was to examine adolescents in the early stages of the disorder to observe primary structural brain abnormalities. METHODS Gray and white matter were measured in 13 adolescents with schizophrenia and 13 healthy controls matched for age, gender, handedness, and school type using voxel-based morphometry. RESULTS Subjects with schizophrenia displayed decreased gray matter in the cerebellar vermis, and alterations in the left putamen and in several parts of the visual system. CONCLUSIONS These findings support cerebellar involvement in the pathogenesis of schizophrenia, and the alterations observed in several parts of the visual system may provide insights into the nature of hallucinations and delusional interpretations.